2002
DOI: 10.1177/1534735402238188
|View full text |Cite
|
Sign up to set email alerts
|

Attachment and Cancer: A Conceptual Integration

Abstract: Cancer traditionally has been explained by the biomedical model; however, it is limited in comprehensively accounting for all factors in this disease. Recently, it has been suggested that a broader theoretical framework that includes psychosocial components in cancer is needed to complement the traditional approach. The purpose of this article, therefore, is to explore the utility of attachment theory as a biopsychosocial model of both development and health. Attachment, a developmental theory, explains how re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 74 publications
0
14
0
3
Order By: Relevance
“…Several studies have shown that the effect of insecure attachment on health‐related outcome is moderated by the perception of social support . This underlines the intertwined relationship between the concepts of social support and attachment that have been described in several theoretical papers examining the applicability of attachment theory to somatic health care . According to these researchers, the core function of the attachment system is to form strategies that serve the purpose of attracting attention when in need of support and soliciting care .…”
Section: Resultsmentioning
confidence: 94%
“…Several studies have shown that the effect of insecure attachment on health‐related outcome is moderated by the perception of social support . This underlines the intertwined relationship between the concepts of social support and attachment that have been described in several theoretical papers examining the applicability of attachment theory to somatic health care . According to these researchers, the core function of the attachment system is to form strategies that serve the purpose of attracting attention when in need of support and soliciting care .…”
Section: Resultsmentioning
confidence: 94%
“…One example of this interest is Tacon's consideration of attachment theory in cancer patients, 29 particularly the relationship between "Type C" individuals (who are cooperative, overly patient, unassertive, and appeasing), 30 avoidant attachment, and the interaction of these factors on medical illness. Other authors have also commented on decreased immunological function and the association to loneliness, divorce, and bereavement.…”
Section: Attachmentmentioning
confidence: 99%
“…Parental care may also have a role in determining vulnerability to disease, including cancer development and progression [10]. In fact, early stress experienced through attachment relations may sensitize the individual to potential stressors later in life [11], and determine how life events have an impact on cancer-related pathways.…”
Section: Introductionmentioning
confidence: 99%